New Neutral Section Automatic Passing Control of Shenhua HXD1 Electric Locomotive - Yong ZHENG; Xueming LI; Jing YUAN; Xiangtao DONG (机车电传动)
In view of the fact that most of the power supply phase separation sections of Shenshuo railway are on long ramps, the traditional way of passing phase for electric locomotives had the problems of large speed loss and long passing time. As a new technology of passing phase with electricity, the electronic switch passing phase had been applied in Shenshuo railway for the first time. In order to adapt to the rapid commutation of electronic switches, the control mode of Shenhua electric locomotive had been optimized accordingly. In the heavy-haul test, the working conditions of traction, braking and inertia of the train could realized fast and fault-free through the phase separation zone without power off. The test results showed that Shenhua electric locomotive could adapt to the way of automatic phase passing based on electronic switch with almost no loss of speed and improved the transportation capacity of heavy haul railway.